INTERNATIONAL ENVIRONMENTAL LAW AND CONSERVATION SCIENCE - prasad, DeepaliAmb; Prasad, Sanjay (International Journal of Research -GRANTHAALAYAH, 2015)
This paper work on international law the body of international law regulating human interaction with the natural world, little of the governance of natural resources, for example, is ‘environmental’. Subsisting at the periphery, environmental law focuses on conserving particular species and ‘ecosystems’, and curbing certain kinds of pollution. Its principles are vague, peppering the margins of rulings within other judicial. The existing methods are slow, cumbersome, expensive, uncoordinated and uncertain. Something better must be found if the environmental challenges the world faces are to be dealt with successfully. Unless we devise a better way to make international law for the environment, future progress is likely to be piecemeal, fitful, unsystematic and even random. The justification for taking bold steps now rests on analysis of three factors: the formidable nature of the environmental issues that must be dealt with; the condition of international organization relating to the environment, particularly the United Nations system; and the methods currently used to make international environmental law. In this paper, we suggest that international environmental laws are due to two competing heritages. The ‘natural world as sacred, inviolable, and redemptive.